Monitoring Poverty trends in Ireland: Results from the 2001 Living in Ireland Survey - Whelan, Christopher T; Layte, Richard; Maitre, Bertrand; Gannon, Brenda; Nolan, Brian; Watson, Dorothy; Williams, James (ESRI, 2003)
The ESRI's study updates our picture of poverty in Ireland using results from the Living in Ireland Survey carried out in 2001. The publication is the latest in a series monitoring living standards and assessing progress towards achieving the targets of the National Anti-Poverty Strategy. It describes trends in the extent of poverty, profiles those affected, and recommends how to monitor poverty in the future as living standards change.